Investigating group-based classes ('weaning workshops') to support complementary infant feeding in Irish primary care settings: a cross-sectional survey. Issue 8 (9th August 2022) - Flannery, Caragh; Shea, Caroline; O'Brien, Yvonne; O'Halloran, Joanne; Matvienko-Sikar, Karen; Kelly, Colette; Toomey, Elaine
Abstract: Objective: This study aims to (1) investigate current practice regarding 'weaning workshops' to support complementary infant feeding delivered within Irish primary care, (2) explore the experiences and opinions of community dietitians regarding optimal content and modes of delivery of weaning workshops and (3) identify the key factors to be considered in the development and implementation of weaning workshops delivered within primary care. Design: Cross-sectional survey. Setting: Irish primary care. Participants: Forty-seven community-based dietitians. Results: Sixteen dietitians reported that workshops were run in their area with variable frequency, with ten reporting that workshops were never run in their area. Participants reported that mostly mothers of medium socio-economic status (SES) attended weaning workshops when infants were aged between 4 and 7 months, and that feedback from workshop attendees was predominantly positive. Dietitians identified that key factors to be considered in future development and delivery of weaning workshops are (1) workshop characteristics such as content, timing and venue, (2) organisational characteristics such as availability of resources and multidisciplinary involvement and (3) attendee characteristics such as SES. Conclusions: This study highlights substantial variability regarding provision of weaning workshops in Ireland, and a lack of standardisation regarding the provider, content and frequency of workshops where workshops are being delivered. The study also provides unique insights into the experiences and opinions of primary care community dietitians regarding the development and delivery of weaning workshops in terms of optimal content and delivery options. These perspectives will make a valuable contribution given the dearth of evidence in this area internationally.